2015
DOI: 10.1111/jcms.12260
|View full text |Cite
|
Sign up to set email alerts
|

European Integration and Outward FDI from Central and Eastern Europe – Is There Any Evidence of Knowledge‐seeking?

Abstract: The European Union (EU) Member States in central and eastern Europe (CEE) witnessed a surge in outward foreign direct investment (OFDI) between 2000 and the start of the global financial crisis. This article investigates whether the European integration process altered the relative importance of host country location factors. In particular, we investigate to what extent knowledge‐seeking is a relevant investment motive, which has been documented as a key determinant for OFDI from other emerging economies. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Therefore, investments in riskier locations are not unusual. The internationalization process of companies from emerging markets is different than in other countries (Jindra et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 92%
“…Therefore, investments in riskier locations are not unusual. The internationalization process of companies from emerging markets is different than in other countries (Jindra et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 92%
“…Also, Stoian (2013) pointed out the differences between post-communist and emerging multinationals. Jindra et al (2015) showed the changes in the location of outward FDI from the CEE after their accession to the EU, but underlined that the main motivations of the CEE multinationals remained market-seeking, with some increased importance of efficiency-seeking, and still negligible knowledge-seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Pull factors, i.e. motivations include mainly market-seeking (Gorynia et al 2015), and there does not seem to be a change Acta Oeconomica 69 (2019) towards strategic asset seeking aims over time (Jindra et al 2015). In many areas, CEE multinationals seem to differ from both their developed and emerging country counterparts (Svetličič 2004), though this difference seem to whither over time (Sass 2018).…”
Section: Introduction To the Special Issue On The Internationalisation Of Central And Eastern European Firmsmentioning
confidence: 99%